The MMSE Algorithm and Mutual Coupling for Adaptive Arrays - Zhiyong Huang; Balanis, C.A. (IEEE transactions on antennas and propagation, 2008)
In this paper, the minimum-mean-square-error (MMSE) in a mutual coupling (MC) environment is derived. The MMSE is slightly degraded by MC with receiver noise but it is not affected with environmental noise. Analysis also shows that data domain MC compensation cannot improve the minimum MSE even if the estimate of MC is accurate. The simulations also show that MC slows down the convergence of the least mean square algorithm.